Construindo o negro : lugares, civilidades e festas em Vitória da Conquista/BA (1870-1930) - Nascimento, Washington Santos (2008)
This thesis has the purpose to discuss the creation of "social places" for african-descendant population, the region of Vitoria da Conquista, located in the southwest municipality of Bahia, in the period between 1870 and 1930. These places were defined by racism, by socio-economic differences, the ideology of money (even diffuse and not systematized), and also, for reasons of morality, honor and different notions of civility. Anchored in the discussions offered by the social representations and cultural studies, deepened the debate on the creation of these "posts" and "counter-posts" and "between-posts" on the basis of everyday conflicts subscribers, especially in cases crimes and newspapers and reviews of festivals, when most of the social interaction of members of that society